Metronidazole Encephalopathy EEG Features: A Case Report with Systematic Review of the Literature - Ricci, Lorenzo (Brain Sci, 2020)
Metronidazole-induced encephalopathy (MIE) is a rare and often under-recognized iatrogenic condition. The diagnosis should be considered in metronidazole-treated patients presenting with acute encephalopathy, unprovoked seizures and cerebellar signs. While typical magnetic resonance imaging (MRI) findings strongly support the diagnosis, electroencephalography (EEG) features have been rarely reported and poorly described. We present a longitudinal EEG assessment in one patient with encephalopathy due to metronidazole toxicity who presented a peculiar EEG pattern presentation and evolution. During the acute phase of encephalopathy, the EEG showed a monomorphic, sharply contoured theta activity symmetrically represented over frontal regions with an anterior–posterior progression which evolved in parallel with clinical worsening. Together with a systematic review of the literature, we discuss whether this EEG activity may represent a distinct neurophysiological correlate of ‘cerebellar encephalopathy’.